Indonesia PENYERTAAN MODAL USAHA PEMBERDAYAAN MELALUI PEMBUATAN USAHA WARUNG “PECEL, JUS, DAN ANEKA MINUMAN (MAE SARINAH)” - Nazaliah Yusma Zahrani; Azmi, Dhiyaa; Rafa Maritza (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
This community service activity aims to empower underprivileged families, particularly focusing on women as heads of households, through business capital assistance. The study uses a Participatory Action Research (PAR) approach to identify and support needy families in lower-middle economic environments. The team selected three families, with Mrs. Sarinah chosen as the primary beneficiary due to her urgent needs. Mrs. Sarinah, a skilled cook, struggled to start a business due to insufficient capital and debt burdens. The program provided her with funds and resources to establish a small stall selling "Pecel, Jus, and Various Drinks" in East Jakarta. The process included fundraising, purchasing necessary items, and continuous monitoring and evaluation to ensure the business's success and sustainability. The program has successfully increased Mrs. Sarinah's family income, proving the effectiveness of the empowerment initiative. This case study highlights how targeted support and collaborative efforts can significantly improve the welfare of underprivileged families, enabling them to achieve economic independence and better living conditions.